Schistosome migration in the definitive host. - Catherine S Nation; Akram A Da'dara; Jeffrey K Marchant; Patrick J Skelly (Public Library of Science (PLoS), 2020)
Schistosomes are parasitic blood flukes that infect >200 million people around the world. Free-swimming larval stages penetrate the skin, invade a blood vessel, and migrate through the heart and lungs to the vasculature of the liver, where maturation and mating occurs. From here, the parasite couples migrate to their preferred egg laying sites. Here, we compare and contrast what is known about the migration patterns within the definitive host of the three major species of human schistosome: Schistosoma mansoni, S. japonicum, and S. haematobium. We conclude that intravascular schistosomes are inexorable colonizers whose migration and egg laying strategy is profligate; all three species (and their eggs) can be found throughout the mesenteric venules, the rectal venous plexus, and, to a greater or lesser extent, the urogenital venous plexuses. In addition, it is common for parasite eggs to be deposited in locations that lack easy access to the exterior, further demonstrating the relentless exploratory nature of these intravascular worms.